The digitised public sphere - Marden, Peter (Javnost (Ljubljana), 2011)
Does an increasingly interconnected world provide new opportunities for civil society to enhance democratic practice - or are human relationships diminished and emptied of their vitality as carefully constructed online profiles proliferate? Debates have emerged about the efficacy of a digital democracy and its ramifications for public politics. This paper follows the specific argument concerning some of the claims from online proponents of the potential of the Internet to create a more informed and accountable democratic culture. It is concerned with questions of the transmission of values and some of the cognitive aspects of this technology. Some techno-futurists are in no doubt concerning the political implications of a more interconnected age; others are more sanguine about the intrusiveness of this new technology. For example, there are numerous claims concerning the potential for Internet-based forums to enrich democratic practice, of breaking-down sovereign borders and establishing a pluralistic transnational global public sphere. On the other hand, political realists are skeptical of new communications technology and its potential to transform democratic life, which is still essentially embedded in the polity of nation states. This paperdoes not add to this burgeoning literature, but rather focuses on "democratic values" by posing questions about "digital democracy" and whether or not this new technology is leading to greater levels of public participation, social inclusion and empathy.
Keywords: javna sfera; civil society; civilna družba; democracy; demokracija; komunikacijska tehnologija; elektronski mediji; sociologija komunikacij